RECENT STUDY ON KALINGA STYLE ARCHITECTURE OF TWO SHAIVA TEMPLES OF EASTERN ODISHA IN INDIA - Ratnakar Mohapatra (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The extant temples of the coastal belt of Odisha represent the Kalinga style temple architecture of India. In fact, the architectural features of some of the Shaiva temples of the Eastern part of Odisha have not been documented by the art historians as well as archaeologists. Here, two Shaiva temples of the Eastern part of Odisha are taken for scholarly discussion. These Shaiva temples are such as 1, Pingalesvara temple of Pokharigaon. 2. Aisanesvara temple of Baligotha respectively. The present temple of Pingalesvara of Pokharigaon is renovated in the last part of the 20th century. It represents a good specimen of the rekha type temple of the Kalinga style architecture of Odisha in Eastern India. This temple is remarkable by its elegant and graceful features. Though the Aisanesvara temple of Baligotha is a small pidha type of deula , still it is a reminiscence of the monument of Gajapati period of medieval Odisha. Both of these temples have not been dealt by other art historians in detail. The present paper attempts to highlight the architectural features along with the religious importance of these two Shaiva temples of the Eastern Odisha in India. Both the primary and secondary sources have been methodologically utilized for the writing of the present article.